Can antibody conjugated nanomicelles alter the prospect of antibody targeted therapy against schistosomiasis mansoni? - Eglal I Amer; Sonia R Allam; Aceel Y Hassan; Esmail M El-Fakharany; Mona M Agwa; Sherine N Khattab; Eman Sheta; Marwa H El-Faham (Public Library of Science (PLoS), 2023)
Background CLA (conjugated linoleic acid)-mediated activation of the schistosome tegument-associated sphingomyelinase and consequent disruption of the outer membrane might allow host antibodies to access the apical membrane antigens. Here, we investigated a novel approach to enhance specific antibody delivery to concealed surface membrane antigens of Schistosoma mansoni utilising antibody-conjugated-CLA nanomicelle technology. Methodology/principal findings We invented and characterised an amphiphilic CLA-loaded whey protein co-polymer (CLA-W) as an IV injectable protein nanocarrier. Rabbit anti-Schistosoma mansoni infection (anti-SmI) and anti-Schistosoma mansoni alkaline phosphatase specific IgG antibodies were purified from rabbit sera and conjugated to the surface of CLA-W co-polymer to form antibody-conjugated-CLA-W nanomicelles (Ab-CLA-W). We investigated the schistosomicidal effects of CLA-W and Ab-CLA-W in a mouse model of Schistosoma mansoni against early and late stages of infection. Results showed that conjugation of nanomicelles with antibodies, namely anti-SmI, significantly enhanced the micelles' schistosomicidal and anti-pathology activities at both the schistosomula and adult worm stages of the infection resulting in 64.6%-89.9% reductions in worm number; 72.5-94% and 66.4-85.2% reductions in hepatic eggs and granulomas, respectively. Treatment induced overall improvement in liver histopathology, reducing granuloma size and fibrosis and significantly affecting egg viability. Indirect immunofluorescence confirmed CLA-W-mediated antigen exposure on the worm surface. Electron microscopy revealed extensive ultrastructural damage in worm tegument induced by anti-SmI-CLA-W. Conclusion/significance The novel antibody-targeted nano-sized CLA delivery system offers great promise for treatment of Schistosoma mansoni infection and control of its transmission. Our in vivo observations confirm an immune-mediated enhanced effect of the schistosomicidal action of CLA and hints at the prospect of nanotechnology-based immunotherapy, not only for schistosomiasis, but also for other parasitic infections in which chemotherapy has been shown to be immune-dependent. The results propose that the immunodominant reactivity of the anti-SmI serum, Schistosoma mansoni fructose biphosphate aldolase, SmFBPA, merits serious attention as a therapeutic and vaccine candidate.